Function and regulation of the PDK1 kinase - Alessi, Dario (Henry Stewart Talks, 2010)
Physiological functions and signaling pathways of insulin, Role of GSK3 in the insulin signaling cascade, Regulation of GSK3 by insulin via PI3K and PKB/Akt, PKB as a key mediator of insulin signaling responses, Exploring the mechanism of PKB activation by PI3K and PDK1, Molecular mechanism of PKB activation, exploring the role of PDK1 in GSK3 regulation by insulin, Studying the model of GSK3 regulation in vivo, Insulin effects mediated by several protein kinases, PDK1 as a "master upstream kinase", Regulation of the PDK1 pathway, The physiological role of PIP3 binding to PDK1, The role of the PDK1 in cancer, Evaluation of PDK1 as a drug target for the treatment of cancer